Investigation of Some Issues of Full Optical Multimedia Networks - Sabol, Dusan; Dubovan, Jozef; Markovic, Miroslav; Dado, Milan (Communications - Scientific letters of the University of Zilina, 2008)
Deployment of optical communication technologies into the core networks has allowed improvements in the transmission characteristics. Further penetration towards the end-user customers has brought online multimedia services. Increasing demand for a quality of service and new types of multimedia services challenges current state of the art technologies and drives not only coming technological trends. Recently emerging DPSK (Differential Phase Shift Keying) format is described and impact of OSNR (Optical Signal to Noise Ratio) level and laser linewidth on its performance is investigated in the environment of Virtual Photonics simulation software. Behavior of used modulation format within WDM (Wavelength-Division Multiplexing) system is examined at four channel’s WDM system.